Pengaruh Media Pembelajaran Berbasis Teknologi AI Terhadap Kemampuan Menulis Puisi Siswa Kelas V SD Negeri Perdamaian - Ruhamma; Nia Astuti; Muhammad Haris Mustaqim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The poetry writing ability of fifth-grade students at Perdamaian State Elementary School is still relatively low. Students have difficulty developing ideas, choosing the right diction, and expressing ideas creatively. In addition, the use of less varied learning media causes poetry writing learning to not take place optimally. Therefore, learning media based on Artificial Intelligence (AI) technology is used as an alternative to improve students' poetry writing ability. This study aims to determine the effect of Artificial Intelligence (AI) technology-based learning media on the poetry writing ability of fifth-grade students at Perdamaian State Elementary School. This study uses a quantitative approach with a quasi-experimental type and a Nonequivalent Control Group Design. The study was conducted at Perdamaian State Elementary School, Bener Meriah Regency in the 2025/2026 Academic Year. The research sample consisted of 32 students consisting of 16 students in the experimental class and 16 students in the control class. Data collection techniques were carried out through poetry writing ability tests in the form of pretests and posttests. Data analysis used normality tests, homogeneity tests, N-Gain analysis, and Independent Samples t-Test hypothesis tests. The results showed that the average posttest score for the experimental class was 86.25, higher than the score for the control class (66.88). The hypothesis test yielded a 2-tailed significance level of 0.000 < 0.05. The N-Gain analysis showed an average score for the experimental class of 74.99% and a score for the control class of 33.64%. Therefore, AI-based learning media significantly and effectively improved the poetry writing skills of fifth-grade students at Perdamaian State Elementary School.